THE ROLE OF EMPOWERMENT ON COMPETENCE TOWARDS EMPLOYEE WORK PERFORMANCE SYARIAH BUSINESS UNIT PT. BANK SINARMAS IN KEDIRI BRANCH - Harnani, Sri; Ng, Beny (Manajemen & Bisnis Jurnal, 2019)
This research analyzes the direct effect of competence on employee empowerment, the direct effect of competence on employee work performance, the direct effect of employee empowerment on employee work performance and the indirect effect of competence on employee work performance through employee empowerment at Syariah Business Unit PT. Bank Sinarmas in Kediri Branch. This research is a quantitative research. The sample used in this study was total sampling method. Data collection methods used questionnaires and data analysis techniques used path analysis. The results show that: 1) Competence has significant direct effect on employee empowerment and employee work performance. 2) Employee empowerment does not have effect on employee performance. 3) Competence does not have effect on employee work performance through employee empowerment. Keywords: Competence, employee empowerment, and employee work performance